2005
DOI: 10.1007/s11661-005-0211-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress-corrosion-crack initiation and growth-rate studies on titanium grade 7 and alloy 22 in concentrated groundwater

Abstract: The stress-corrosion-crack initiation and growth-rate response was evaluated on as-received, coldworked, and aged Alloy 22 (UNS N06022) and titanium Grade 7 in 105 °C to 110 °C, aerated, concentrated, high-pH groundwater environments. Time-to-failure experiments on actively loaded tensile specimens evaluated the effects of applied stress, welding, surface finish, shot peening, cold work, crevicing, and aging treatments in Alloy 22. Titanium Grade 7 and stainless steels were also included in the matrix. Long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…is possible in the low-alloy steel-water system to measure crack velocities much lower than v II , suggesting that K ISCC is not a true constant (Speidel, 1984) but rather has a value dependent on the crack velocity, which is regarded as insignificant. This varies between laboratories, but it is common to use 10 -11 m/s, the lowest easily measured crack velocity, as a criterion for insignificant SCC (Andresen, Angeliu, & Young, 2001;Andresen, Young, Catlin, & Gordon, 2005;Toloczko, Andresen, & Bruemmer, 2007).…”
Section: Figurementioning
confidence: 99%
“…is possible in the low-alloy steel-water system to measure crack velocities much lower than v II , suggesting that K ISCC is not a true constant (Speidel, 1984) but rather has a value dependent on the crack velocity, which is regarded as insignificant. This varies between laboratories, but it is common to use 10 -11 m/s, the lowest easily measured crack velocity, as a criterion for insignificant SCC (Andresen, Angeliu, & Young, 2001;Andresen, Young, Catlin, & Gordon, 2005;Toloczko, Andresen, & Bruemmer, 2007).…”
Section: Figurementioning
confidence: 99%
“…Crack length vs. time was monitored in-situ using a reversing direct current (DC) potential drop technique. The crack growth rate was approximately 1.3 × 10 -11 m/s [15,16].…”
Section: Discussionmentioning
confidence: 96%
“…For example, slow strain rate tests of Alloy 22 in BSW-13 solution at 105°C did not show any signs of stress corrosion cracking, even at the highest polarization potentials of +400 mV SSC (saturated silver chloride) [14]. Andresen et al used cyclic and constant loads to test compact tension Alloy 22 fatigue in pre-cracked specimens in BSW solution at 110°C [15]. They tested both 20% cold worked and thermally aged specimens at a stress intensity level of 30 to 45 MPa√m and reported extremely low crack growth rates on the order of 2-8 x 10 -13 m/s [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of EAC in alloy 600 in deaerated high purity water with various levels of dissolved hydrogen at temperatures in the range from 315 to 360uC, Richey et al 63 compared DCPD, linear variable differential transformer measurements and ECN. They use active loading (electric actuator or dead weights), pressure loading ('Keno' 64 ) and ring loading, an arrangement whereby the ring shaped specimen is pulled along the direction of its diameter to a predetermined load and then locked in position before exposure, which is expected to lead to specimen creep at the temperature of interest. They reported that DCPD was able to give a reliable indication of EAC occurrence, correctly showing changes in slope when EAC occurred, whereas no changes were detected by EN and the linear variable differential transformer associated with the ring.…”
Section: Applications Of Technique In Eac and Initiation Researchmentioning
confidence: 99%